Tacrolimus 0.1% ointment in nail psoriasis: a randomized controlled open‐label study. (13th July 2012) - De Simone, C.; Maiorino, A.; Tassone, F.; D'Agostino, M.; Caldarola, G.
Abstract: Background  Despite recent advances in the treatment of psoriasis, the therapeutic options for nail psoriasis are very limited, particularly when this is the only manifestation of the disease. Objective  We performed a randomized controlled open‐label study to assess the efficacy and safety of a topical treatment with tacrolimus 0.1% ointment in nail psoriasis. Methods  In each patient, tacrolimus 0.1% ointment was prescribed for application only on the affected nails of a randomly selected hand for 12 weeks, whereas nails of the other hand did not receive any treatment. Severity of nail psoriasis was evaluated using the Nail Psoriasis Severity Index (NAPSI) score. Results  We enrolled 21 consecutive psoriatic patients. At week 12, a statistically significant ( P  < 0.001) improvement was obtained in the treated hands with respect to the hands used as control (NAPSI score absolute change 13.0 and 3.0 respectively). Each of the enrolled patients concluded the period of treatment, but one patient was withdrawn from tacrolimus application after 9 weeks because of the appearance of acute paronychia. Discussion  Our study showed that tacrolimus 0.1% ointment may be an efficacious and safe therapeutic opportunity in the treatment of nail psoriasis. Our data should be confirmed by a double‐blind study with a larger sample of patients.